2012
DOI: 10.2147/jir.s26917
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes complications and leukocyte counts in Iranian patients

Abstract: BackgroundThe long term complications of diabetes can be fatal. They are also renowned for being an economic burden. Previous studies have demonstrated a relationship between inflammatory markers and complications of diabetes. The objective of this study was to evaluate the relationship between leukocyte counts and these complications.MethodsThe study included 184 patients diagnosed with type 2 diabetes. The study was carried out in Iran during 2007 and 2008. Data collected on the subjects were as follows: age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
2
29
1
1
Order By: Relevance
“…In addition, in an effort to isolate the primary influence of WBC, we studied adults free of other cardiometabolic risk factors that have been shown to influence WBC and endothelin-1 system activity such as hypertension 21 and type 2 diabetes. 26,27 Although the plasma concentrations of CRP were slightly, but not significantly, higher in the WBC group, we do not believe that these higher CRP concentrations influenced our findings, and in turn, the interpretation the data. Indeed, in the present study we observed no relation between CRP and either WBC or the FBF responses to ET-1 or BQ-123.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, in an effort to isolate the primary influence of WBC, we studied adults free of other cardiometabolic risk factors that have been shown to influence WBC and endothelin-1 system activity such as hypertension 21 and type 2 diabetes. 26,27 Although the plasma concentrations of CRP were slightly, but not significantly, higher in the WBC group, we do not believe that these higher CRP concentrations influenced our findings, and in turn, the interpretation the data. Indeed, in the present study we observed no relation between CRP and either WBC or the FBF responses to ET-1 or BQ-123.…”
Section: Discussioncontrasting
confidence: 60%
“…To date, numerous studies have shown that high total leukocyte count at baseline is associated with later development of type 2 diabetes and poor health outcomes in older adults [17,24,29,32,45,48]. Furthermore, many studies have demonstrated that higher total leukocyte count is linked to metabolic syndrome, but the association between differential leukocyte count and this chronic condition is still unclear.…”
Section: Leukocyte Count and Insulin Resistancementioning
confidence: 99%
“…There are studies indicating that an elevated WBC count, even within the normal range, is associated with both macro- and microvascular complications in type 2 diabetes 6. Higher WBC counts may be associated with the development of retinopathy, albuminuria, and peripheral arterial disease 7-9. Previous studies have paid much attention to proinflammatory cytokines but little to the routine and reliable WBC count.…”
Section: Introductionmentioning
confidence: 99%